Sugammadex: a novel approach to reversal of neuromuscular blockade. (February 2011) - Aniskevich, Stephen; Leone, Bruce J; Brull, Sorin J
Sugammadex is the first in a new class of medications termed selective relaxant binding agents. This medication acts to encapsulate free circulating steroidal nondepolarizing neuromuscular blocking agents. The encapsulation of neuromuscular agents effectively decreases the amount of neuromuscular blocker interacting at the neuromuscular receptor. This binding has a very high association rate, rendering the incidence of residual block extremely low, while avoiding the side effects associated with traditional reversal agents. Currently approved for clinical use in over 50 countries, sugammadex was not approved by the US FDA in 2008 due to concerns over potential hypersensitivity reactions. It is hoped that further study and clinical experience will help to better define the risk associated with sugammadex and eventually lead to the approval of this novel medication in the USA.